THE ROLE OF EXPERT WITNESSES IN COMPENSATION OF NON – PECUNIARY DAMAGE PROCEEDINGS IN THE LEGAL SISTEM OF THE REPUBLIC OF SERBIA (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
Protection of violated or endangered rights and determination of facts in court proceedings often go beyond the field of law and require the involvement of experts in other fields. In dealing with technical, medical, economic, and other issues, expert witnesses are hired whose findings and opinions can be crucial and influence the final court decision. For this reason, it is important that the expert witness has human and professional qualities that qualify him for the expert witnessing job. The existing legal solutions do not envisage training or the obligation of continuous professional development of expert witnesses, which may adversely affect the quality of expertise and the efficiency of court proceedings. In this respect, it is necessary to improve the existing legal framework and to categorize and license the expert witnesses in order for their engagement to be in accordance with court requirements. In addition to the training of expert witnesses, it is necessary to improve the training of judges. For the purposes of deciding in intangible damage compensation proceedings, judges must be aware of medical law, as lack or insufficient knowledge of medical law can be the reason for accepting expert witness findings without objection.